Understanding and increasing Right First Time (RFT) Performance in a production environment: a case study - Gregoire, Carrie (Kansas State University, 2017)
It is estimated that the animal health biologics sector will increase by over 27% between 2015 and 2020. This projection and the increasing competition among the sector’s players suggests need to find ways to enhance their efficiencies in manufacturing to sustain their relative competitiveness. One approach to enhancing efficiencies is to ensure that all work is done once, i.e., everything is done right the first time. This research focused on human error as a major source of inefficiency in manufacturing and hypothesized that addressing issues that reduce human error would contribute to reducing inefficiencies. The research used the Kaizen process to assess the before and after counts of human error in a biologics manufacturing unit of Z Animal Health Company (ZAHC). The study found that human error accounted for about 51% of all sources of error in the pre-Kaizen period and only about 34% of all errors in the post-Kaizen period, a reduction in excess of 33.3%. Given that humans are directly or indirectly responsible for all activities in the manufacturing process, the Kaizen process also contributed to a reduction in most other error sources. For example, errors in raw materials and components went reduced by about 50%. We tested the hypothesis that undertaking the Kaizen was statistically effective in reducing human error compared to all other errors using a logit model. Our results confirmed this hypothesis, showing that the odds ratio of human error in the post-Kaizen period was about 50% of the odds of non-human error. The research suggests that in a highly technical manufacturing environment, such as in animal health biologics, human errors can be a major problem that can erode competitiveness quickly. Focusing employees’ on root causes of errors and helping them address these through structured quality-enhancing initiatives such as Kaizen produce superior results. It is, therefore, suggested that when organizations discover human error as a major source of inefficiency, it is prudent to help employees understand what they do and how what they do contributes to the overall performance of the organization. This appreciation of how their actions fit into the big picture could provide a foundation upon which significant improvements can be achieved.
Keywords: Kaizen; Right First Time; Human Error; Biologics